El cuento infantil y su relación con el desarrollo del lenguaje oral de las niñas y niños del primer grado del centro de educación básica Primicias de la Cultura de Quito plantel central de la red educativa Q-6 de la provincia Pichincha, cantón Quito. Período lectivo 2013-2014. Lineamientos propositivos - Vega Vargas, Mariela Genoveba (2014)
This thesis refers to: CHILD STORY AND ITS RELATION TO THE DEVELOPMENT OF ORAL LANGUAGE OF GIRLS AND CHILDREN FIRST GRADE BASIC EDUCATION CENTER FIRST PRIMICIAS DE LA CULTURA DE QUITO OF QUITO CENTRAL CAMPUS EDUCATIONAL NETWORK Q-6 PROVINCE PICHINCHA, CANTON QUITO. LECTIVO PERIOD 2013-2014 ". GUIDELINES proactive. The overall objective of this research was: To analyze the relationship between the Children's Story and Oral Language Development of children from the first grade of Basic Education. The methods used were: Scientist, Inductive-Deductive, Analytic-Synthetic and Statistical Model; the techniques applied were: ranging from pre surveys for teachers if they use the Children's Story in the daily work with children; Zimmerman Test applied to children from First Year of Basic Education to determine the development of oral language. From the information obtained from the survey, came to the conclusion that 100% of teachers ranging from pre surveyed, using the Children's Story in the daily work with the children and the type of stories that use the surveyed teachers are: 100 % responded, using Adventure Tales and Fantasy, by 50% and the dramatic tale with children First-Year Basic Education stories. According to the application of test Zimmerman applied to evaluate children for Oral Language Development concluded that 56% of children scored at 30-40 corresponding to the rating of Normal; 12% of children investigated average score was 50 to 80 that corresponds to the rating of Excellent and 32% of children had a score of 10 to 20 that corresponds to the rating of Low